Strengthening Pancasila Values-Based Digital Literacy in Pancasila Education Learning in Elementary Schools - Nurul Hasanah; Elizar; Eny Munisah (Universitas Pendidikan Ganesha, 2026)
The rapid development of digital technology has made digital literacy an essential competence in education; however, its use in elementary schools still faces ethical and responsibility-related challenges. This condition highlights the need to integrate digital literacy with Pancasila values in Pancasila Education learning. This study aims to analyze and synthesize research findings related to strengthening Pancasila-based digital literacy in learning. This study employs a Systematic Literature Review (SLR) method using the PRISMA framework. Data were collected through the search of scientific articles in the Google Scholar database based on specific inclusion criteria within a recent publication range, resulting in 10 selected articles for analysis. Data analysis was conducted using a qualitative descriptive approach and thematic synthesis. The results show that strengthening Pancasila-based digital literacy is implemented through the use of interactive digital learning media, digital literacy based learning models, the development of digital literacy culture, and the use of digital literacy control instruments. However, the effectiveness of its implementation is still influenced by teacher competence, the availability of systematic guidelines, and institutional support. This study concludes that the integration of digital literacy and Pancasila values is an important strategy in shaping students who are both digitally competent and strongly characterized. The findings have implications for the development of more adaptive Pancasila Education learning in the digital era.